Semantic Features of Homonymy and Polysemy in English and Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article studies the challenges posed by homonymy and polysemy in contemporary English and Uzbek. It clarifies the distinctions between these two linguistic phenomena and explores methods for differentiating between words exhibiting homonymy and those exhibiting polysemy in the two languages.